Jack and the Beanstalk - Di Lernia ;Giuseppe (Penguin Random House, 2019)
This traditional fairy tale remains a favorite with parents looking for a children's classics to read with their little one. When Jack sells his cow for a handful of magic beans, he doesn't expect a huge beanstalk to grow outside his window! Join Jack as he goes on an exciting and magical adventure up to the top the towering beanstalk and discovers a hungry giant, a golden goose, and a magical harp. The charming illustrations by Giuseppe Di Lernia in this picture book are sure to capture the imaginations of little ones, and the large format of this book is ideal for sharing with children aged 3 to 5 and reading together at bedtime. Children won't be able to stop themselves from joining in as the giant repeatedly shouts, "Fe-fi-fo-fum. I smell the blood of an Englishman!"